Imaging of pediatric bone and joint trauma - Martino, Fabio; Defilippi, Claudio; Caudana, Roberto (Springer Milan, 2011)
Imaging of Pediatric Bone and Joint Trauma is a multiauthored work dealing comprehensively with the various aspects of imaging of pediatric musculoskeletal trauma. Thebook is ideally subdivided in three main sections: an overview of traumatic lesions; imaging of traumatic injuries according to body region; typical traumatic injuries of early infancy. This latter section also presents a review of the legal aspects of dealing with child abuse (with specific focus on the ?battered child?), including current international medico-legal guidelines. The book's didactic approach and its wide-ranging account of the subject makes it of value to practitioners from the full range of disciplines involved in the diagnosis and management of pediatric bone and joint trauma.